Energy performance and climate control in mechanically ventilated greenhouses: A dynamic modelling-based assessment and investigation. (15th April 2021) - Costantino, Andrea; Comba, Lorenzo; Sicardi, Giacomo; Bariani, Mauro; Fabrizio, Enrico
Highlights: A new model for estimating the energy consumption of greenhouses is provided. A plant model is coupled to consider the crop effects on thermal and mass balances. The proposed model allows the user to simulate also variable angular speed fans. The model was successfully validated against real monitored data. Electrical energy consumption decreases by 25% using variable angular speed fans. Abstract: Controlled environment agriculture in greenhouse is a promising solution for meeting the increasing food demand of world population. The accurate control of the indoor environmental conditions proper of greenhouses enhances high crop productivity but, contemporarily, it entails considerable energy consumption due to the adoption of mechanical systems. This work presents a new modelling approach for estimating the energy consumption for climate control of mechanically ventilated greenhouses. The novelty of the proposed energy model lies in its integrated approach in simulating the greenhouse dynamics, considering the dynamic thermal and hygric behaviour of the building and the dynamic response of the cultivated crops to the variation of the solar radiation. The presented model simulates the operation of the systems and the energy performance, considering also the variable angular speed fans that are a new promising energy-efficient technology for this productive sector. The main outputs of the model are the hourly thermal and electrical energy use for climate control and the main indoor environmental conditions. The presented modelling approach was validated against a dataset acquired in a case study of a new fully mechanically controlled greenhouse during a long-term monitoring campaign. The present work contributes to increase the knowledge about the dynamics and the energy consumption of greenhouses, and it can be a valuable decision support tool for industry, farmers, and researchers to properly address an energy efficiency optimisation in mechanically ventilated greenhouses to reach the overall objective of decreasing the rising energy consumption of the agricultural sector.